Towards a competency-based doctoral curriculum at the University of Zambia: lessons from practice - Mumba, Chisoni; Sichone, James Maimbo; Munsaka, Sody; Kwenda, Geoffrey; Munyeme, Musso; Simuunza, Martin; Hang’ombe, Bernard M.; Phiri, Andrew M.; Mutale, Wilbroad; Martin, Marie H.; Heimburger, Douglas C.; Nalubamba, King S.; et al. (Frontiers in Education, 2023)
We describe a collaborative, iterative, and participatory process that we undertook to develop and adopt a competency-based doctoral curriculum framework at the University of Zambia. There needs to be more than the traditional unstructured apprenticeship of PhD training in a knowledge-based economy where PhD graduates are expected to contribute to industry problem-solving. The lack of industry-driven competencies and, to some extent, limited skills possessed by PhD graduates relative to the demands of employers has led to the misclassification of doctoral degrees as mere paper certificates. Further, under traditional PhD training without specific core competencies, it has led to criticisms of such PhD studies as a waste of resources. The calls to rethink doctoral development in broader employment contexts led many countries to redesign their PhD programs. Training has increasingly introduced industrial linkages and industry-defined research projects to increase the attractiveness of doctoral students. Whereas developed countries have made significant reforms towards competencye-based PhD training, little or nothing has been done in developing countries, especially in sub-Saharan Africa. This against the demands that Africa needs more than 100,000 PhDs in the nexta decade to spur economic development. Against this background, the University of Zambia has developed an industry-driven structured competency-based PhD curriculum framework.The framework will guide and support the development of standardized program-specific PhD curricula, delivery, and assessment of competencies at the University of Zambia, ensuring that doctoral students acquire skills and demonstrate core competencies that are transferable and applicable in industry settings. This framework focuses on the development of specific competencies that are necessary for successful PhD completion. The competencies are divided into three main categories: research, teaching, and professional development. Each category is then broken down into ten core competencies from which respective doctoral programs will develop sub-competencies.It is from these core competencies and sub-competencies that learning outcomes, assessment methods, and teaching activities are developed. It is envisioned that this new competency-based doctoral curriculum framework will be a helpful tool in training a cadre of professionals and researchers who benefit the industry and contribute to economic and societal development.